Treatment of lingual gingival recession on mandibular lateral incisor using minimally invasive full-thickness tunneling technique and subepithelial palatal connective tissue graft - Eiti Agrawal; Rahul Chopra; Nikhil Sharma (Wolters Kluwer Medknow Publications, 2021)
Gingival recession on the lingual aspect of teeth may cause dentinal hypersensitivity problems in patients. Treatment of such recessions is not a regular procedure owing to its anatomical restraints, difficulty in isolation as well as lack of esthetic importance. The present case describes the use of connective tissue graft (CTG) in the treatment of isolated lingual recession on mandibular lateral incisor using minimally invasive tunneling technique. Six-month posttreatment follow-up showed a root coverage of 3.5 mm with enhanced width of keratinized tissue. This report encourages the application of CTG along with tunneling technique in the treatment of lingual recession to achieve root coverage as well as alleviate patient's dentinal hypersensitivity issues.